The student movement at the university of Buenos Aires during the early years of the dictatorship in Argentina (1976–1978) - Seia, Guadalupe Andrea (Universidad Nacional del Litoral, 2021)
This article seeks to contribute to the scholarly literature on the student movement and Argentine universities in recent history. We focus on the activism and the organizations of the students at the Universidad de Buenos Aires during the early years of the so–called «Proceso de Reorganización Nacional» (Process of National Reorganization), a dictatorship that lasted between 1976 and 1983. In addition, we describe the positions adopted of by different student and political organizations in response to the policies introduced by the Armed Forces on university matters.